2021
DOI: 10.1371/journal.pone.0261719
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to qualitative data sharing in the United States: A survey of qualitative researchers

Abstract: Qualitative health data are rarely shared in the United States (U.S.). This is unfortunate because gathering qualitative data is labor and time-intensive, and data sharing enables secondary research, training, and transparency. A new U.S. federal policy mandates data sharing by 2023, and is agnostic to data type. We surveyed U.S. qualitative researchers (N = 425) on the barriers and facilitators of sharing qualitative health or sensitive research data. Most researchers (96%) have never shared qualitative data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Yet, studies of data management in the social sciences reported a lack of convergence on norms for preparing qualitative data for deposit (Antes et al, 2018). The heterogeneity of qualitative data can pose challenges to developing generalizable best practices (Elman et al, 2010; Mozersky et al, 2021), a lack of convergence on norms for managing and depositing qualitative data that can lead scientists to improvise data management practices (Bratt, 2022, 2023). For example, scientists' practices of anonymizing data to prepare interview transcripts for deposit can be ad hoc (Crowston & Qin, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, studies of data management in the social sciences reported a lack of convergence on norms for preparing qualitative data for deposit (Antes et al, 2018). The heterogeneity of qualitative data can pose challenges to developing generalizable best practices (Elman et al, 2010; Mozersky et al, 2021), a lack of convergence on norms for managing and depositing qualitative data that can lead scientists to improvise data management practices (Bratt, 2022, 2023). For example, scientists' practices of anonymizing data to prepare interview transcripts for deposit can be ad hoc (Crowston & Qin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, even if there are computational scripts that tell computers how to handle the data (ostensive routines) they are not always specific enough to guarantee an exact execution of the process (performative routines). The social sciences may represent even greater challenges, given the relatively increased heterogeneity of data and ambiguous ostensive routines (or none at all) specifying the data management actions to take (Borgman et al, 2021; Mozersky et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Data sharing mandates may be resisted if qualitative researchers are reticent to share due to concerns about negatively affecting existing relationships between researchers and participants (Mozersky, Walsh, et al, 2020; Mozersky et al, 2021). We conducted a survey of 425 qualitative researchers in the U.S. who gather health related or sensitive data (Mozersky et al, 2021). Only 4% of qualitative researchers had ever shared their data in a repository, and their top concerns regarding qualitative data sharing include the sensitivity of the data (85%) and breach of participant trust (82%).…”
Section: Introductionmentioning
confidence: 99%
“…Data sharing mandates may be resisted if qualitative researchers are reticent to share due to concerns about negatively affecting existing relationships between researchers and participants (Mozersky, Walsh, et al, 2020; Mozersky et al, 2021). We conducted a survey of 425 qualitative researchers in the U.S. who gather health related or sensitive data (Mozersky et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation